Design of short-video-based microlearning for enhancing elementary students’ digital literacy - Silvester Silvester; Totok Victor Didik Saputro; Pebria Dheni Purnasari; Yosua Damas Sadewo; Kusnanto Kusnanto (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2025)
This study analyzes the design of short-video-based microlearning developed by elementary school teachers to strengthen students’ digital literacy in Bengkayang Regency, West Kalimantan. Qualitative case study design was employed in four elementary schools, with data collected through interviews, observations, and documentation and analyzed using Miles and Huberman’s interactive models. The findings show that teachers were able to design microlearning creatively despite limitations in infrastructure and digital devices. The instructional designs focused on a single core concept within a duration of 1–5 minutes and integrated visual, audio, and text elements to support students’ conceptual understanding. Teachers used accessible applications such as Canva, CapCut, and KineMaster and implemented videos through various strategies, including flipped classrooms, introductory activities, and contextual documentation of school activities. The implementation of microlearning proved effective in enhancing students’ focus, engagement, and digital literacy skills, particularly in critically and responsibly interpreting digital information. However, teachers still faced challenges related to unstable electricity and internet access, limited devices, and constraints in video-editing skills. Overall, short-video-based microlearning is an effective and adaptive strategy to support the implementation of the Kurikulum Merdeka in border-area schools and offers an innovative solution for strengthening digital learning in elementary education.